2020
DOI: 10.1186/s12885-020-06861-x
|View full text |Cite
|
Sign up to set email alerts
|

Design of a randomized controlled trial of a partnership-based, needs-tailored self-management support intervention for post-treatment breast cancer survivors

Abstract: Background Self-management is becoming essential for breast cancer survivors, but evidence about the effectiveness of self-management support (SMS) intervention is lacking. To address this issue, we developed a theory-based SMS intervention, the ‘EMPOWER’, aimed at empowering breast cancer survivors. Here we describe the rationale of the intervention and its development. Methods The conceptual framework of this study is the Chronic Care Model, which posits that SMS can influence patient-provider relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…(Cronbach's alpha at baseline for the total score was 0.93 and ranged from 0.71 to 0.90 for the subscales.) We detailed the psychometric properties of the outcome measures elsewhere 23 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(Cronbach's alpha at baseline for the total score was 0.93 and ranged from 0.71 to 0.90 for the subscales.) We detailed the psychometric properties of the outcome measures elsewhere 23 …”
Section: Methodsmentioning
confidence: 99%
“…The trial was registered in the Korean Clinical Research Information Service (KCT0004794). A detailed study protocol has been published elsewhere 23 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 Providing social support had the potential to enhance patients' self-efficacy and self-management capabilities. 47 Our results indicated that the scale had good predictive validity, as the total predictive effect of SMS on self-management behavior was 0.961 ( P < 0.001). Moreover, SMS directly predicted self-management behavior ( β = 0.827, P < 0.001), accounting for 86.1%, and also indirectly influenced self-management behavior through self-efficacy ( β = 0.134, P < 0.001), accounting for 13.9%.…”
Section: Discussionmentioning
confidence: 60%